Advancing Garut Leather Small and Medium Enterprises to a Higher Level: Key Influencing Factors - Ridlwan Muttaqin; Kasir Kasir; Prinska Damara Sastri (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to identify factors influencing the upgrading efforts of leather MSMEs in Garut Regency. A quantitative approach was used by collecting data through questionnaires from 260 leather MSME owners operating in the Sukaregang industrial area using a purposive sampling technique. Data analysis was conducted through partial tests, simultaneous tests, correlation tests, and coefficients of determination to examine the influence of Digital Marketing, Digital Finance, Product Innovation, and Human Resource Capacity on MSME performance. The results showed that partially, Digital Marketing and Digital Finance had no significant effect on MSME performance, while Product Innovation had a negative and significant effect, and Human Resource Capacity had a positive and significant effect. Simultaneously, these four variables were proven to have a significant effect on the performance of Garut leather MSMEs. This finding confirms that increasing human resource capacity is a key factor, accompanied by the implementation of appropriate innovation and digitalization to strengthen the competitiveness and desires of MSMEs. This study provides practical implications for MSME actors and policymakers in developing strategies for developing Garut leather MSMEs so that they can upgrade their class and be competitive.